Prevaccination screening of health-care workers for immunity to measles, rubella, mumps, and varicella in a developing country: What do we save? - Emine Alp; Fatma Cevahir; Selma Gökahmetoglu; Hayati Demiraslan; Mehmet Doganay (Journal of Infection and Public Health, 2012)
Summary: A structured questionnaire was administered to health-care workers (HCWs). The HCWs were also screened for measles, rubella, mumps, and varicella (MMRV) using serological methods. One thousand two hundred and fifty-five HCWs were tested. Of the HCWs examined, 94% were immune to measles, 97% to rubella, 90% to mumps and 98% to varicella. The positive predictive values of histories of measles, mumps, rubella and varicella were 96%, 93%, 100% and 98%, respectively. The negative predictive values of histories of measles, mumps, rubella and varicella were 13%, 17%, 5% and 2%, respectively. The cost of vaccination without screening was significantly more expensive (cost difference: €24,385) for varicella, although vaccination without screening was cheap (cost difference: €5693) for MMR. Although the use of cheaper vaccines supports the implementation of vaccination programs without screening, the cost of vaccination should not be calculated based only on the direct costs. The indirect costs associated with lost work time due to vaccination and its side effects and the direct costs of potential side effects should be considered. However, if prescreening is not conducted, some HCWs (2–7%) would be unprotected against these contagious illnesses because of the unreliability of their MMRV history. In conclusion, the screening of HCWs before vaccination continues to be advisable. Keywords: Immunization, Healthcare worker, Vaccine, Vaccination, Cost